STUDY OF THE RELATIONSHIP BETWEEN 5-6 YEAR-OLD PRE-SCHOOL CHILDREN’S SOCIAL SKILLS AND BEHAVIOR PROBLEMS CONSIDERING THEIR RELATIONS WITH THEIR PARENTS - Hale DERE ÇİFTÇİ (Fırat University, 2019)
Early childhood period is very essential as the children acquire the basic social skills that help them become socially effective i